Ancient Israel and Its Neighbors Interaction and Counteraction - Naʾaman, Nadav 1939- (Penn State University Press, 2006)
Throughout the past three decades, Nadav Na'aman has repeatedly proved that he is one of the most careful historians of ancient Canaan and Israel. With broad expertise, he has brought together archaeology, text, and the inscriptional material from all of the ancient Near East to bear on the history of ancient Israel and the land of Canaan during the second and first millenniums B.C.E. Many of his studies have been published as journal articles or notes and yet, together, they constitute one of the most important bodies of literature on the subject in recent years, particularly because of the careful attention to methodology that Na'aman always has brought to his work.Collected here are 25 essays that focus particularly on ancient Israel's relations with its neighbors and the forces inside the ancient nation that governed those relationships. Subjects range from the battle of Qarqar to the archaeology of the monarchy to the status of governors during the Persian Period
Keywords: HISTORY / Ancient / General